World War I in Thai Plays during the Reign of King Rama VI (1910-1925): Presentation Techniques and Concepts - Pansombut, Chanaphon; Jatuthasri, Thaneerat; Polmuk, Chairat (Journal of Thai Studies, 2024)
Background and objective (s): During the reign of King Rama VI (King Vajiravudh), the period of creation of Thai literary texts about World War I, including non-fiction and fiction, lasted from 1914 to 1924. However, imaginative writings, especially plays, have rarely been studied on the subject of this war, despite the fact that these plays display intriguing literary techniques in conveying various perspectives on World War I. Therefore, this study aimed to examine literary techniques for presenting concepts concerning World War I in Thai plays during the reign of King Rama VI to demonstrate how Thai authors interpreted historical events for literary creation. Methodology: The research for this paper relied on a close literary reading method to analyze textual elements such as plot, characters, settings and poetic devices. This textual analysis was then related to the political contexts during the reign of King Rama VI. Main result: Thai authors presented various aspects of World War I, including warring parties, armaments, strategies and heroes in their various types of popular plays. These aspects of the war were incorporated into elements of the plays, including plot, characters, settings and poetic devices. Through these techniques, the plays conveyed three main concepts concerning World War I, namely, wartime conflict, national security and kingship. All of these concepts can be related to political conflicts during the reign of King Rama VI that involved the status of Siam in World War I and the administrative policies of King Rama VI, among other issues. Relevance to Thai Studies: The research for this article was a sociopolitical study of Thai literature that focused on the relationship between an historical event and the imaginative process in the creation of wartime literary works. Conclusion: Thai plays during the reign of King Rama VI incorporated various aspects of World War I in literary elements of the texts to convey concepts related to the political conflicts at that time, including the status of Siam in World War I and other political conflicts.These plays were, thus, not only literary texts created for entertainment purposes, but also for political reasons, especially to support the monarchy’s national and international policies during that period.